2013
DOI: 10.1038/eye.2013.114
|View full text |Cite
|
Sign up to set email alerts
|

Two-year results of intravitreal ranibizumab for polypoidal choroidal vasculopathy with recurrent or residual exudation

Abstract: Aim To clarify the 2-year efficacy of ranibizumab for patients with polypoidal choroidal vasculopathy (PCV) with recurrent or residual exudation from branching vascular networks after previous photodynamic therapy (PDT). Methods We retrospectively reviewed 26 eyes of 26 Japanese patients (22 men, 4 women) in this pilot study. All eyes had PCV with complete regression of polypoidal lesions resulting from PDT detected by indocyanine green angiography (ICGA), but recurrent or residual leakage from branching vascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Saito et al . 10 reported that ranibizumab was efficacious in patients with PCV with recurrent or residual exudation from BVN after previous PDT. However, the efficacy of aflibercept in recurrent or refractory cases has not been determined.…”
Section: Introductionmentioning
confidence: 99%
“…Saito et al . 10 reported that ranibizumab was efficacious in patients with PCV with recurrent or residual exudation from BVN after previous PDT. However, the efficacy of aflibercept in recurrent or refractory cases has not been determined.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13][14] In a previous study 7 (ClinicalTrials.gov identifier: NCT00837330), we evaluated intravitreal ranibizumab 0.3-and 0.5-mg monotherapy in 20 eyes of non-Asian patients with PCV. Ranibizumab (0.3-and 0.5-mg groups pooled) was well tolerated and resulted in improved best-corrected visual acuity (BCVA; +1.2 Snellen lines at months 12 and 24) and reduced center point thickness (−53 and − 67 μm at months 12 and 24, respectively) in the majority of eyes.…”
Section: Introductionmentioning
confidence: 99%